Nucleocytoplasmic plant lectins - Lannoo, Nausicaä; Van Damme, Els J.M. (Biochimica et biophysica acta, 2010)
During the last decade it was unambiguously shown that plants synthesize minute amounts of carbohydrate-binding proteins upon exposure to stress situations like drought, high salt, hormone treatment, pathogen attack or insect herbivory. In contrast to the ‘classical’ plant lectins, which are typically found in storage vacuoles or in the extracellular compartment this new class of lectins is located in the cytoplasm and the nucleus. Based on these observations the concept was developed that lectin-mediated protein–carbohydrate interactions in the cytoplasm and the nucleus play an important role in the stress physiology of the plant cell. Hitherto, six families of nucleocytoplasmic lectins have been identified. This review gives an overview of our current knowledge on the occurrence of nucleocytoplasmic plant lectins. The carbohydrate-binding properties of these lectins and potential ligands in the nucleocytoplasmic compartment are discussed in view of the physiological role of the lectins in the plant cell.